HUBUNGAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) DENGAN KADAR SGOT DAN SGPT DALAM DARAH PADA PETANI PADI - Iga Maliga; Rafi'ah Rafi'ah (Dian Nuswantoro Semarang, 2021)
The use of personal protective equipment (PPE) when spraying pesticides is a must in agricultural activities. It greatly affects the long-term health conditions of farmers. This study aimed to see the relationship between the use of PPE with SGOT and SGPT levels in the blood of rice farmers. This study used quantitative research with an analytic observational research design using a cross-sectional approach. Blood samples were taken for farmers and carried out the process of filling out questionnaires and observation sheets. The results of the questionnaire were processed with SPSS 16.0, with Fisher's exact test. The sample of the study was 40 rice farmers taken purposively. The results showed that the levels of SGOT and SGPT were more in the normal category. The analysis showed that there was no relationship between AST and ALT levels with the use of PPE. It can be seen from the significance value of more than 0.05. As many as 38.5% complained about recurring complaints. After spraying, dizziness, dizziness, watery eyes, frequent spitting, namely vision, coughing, and ergonomic complaints in the form of back pain and lumbago. The conclusion in this study is that there is no relationship between the use of PPE with AST and ALT levels in the blood.